Menjadi Korean di Indonesia: Mekanisme Perubahan Budaya Indonesia - Korea - Kiki Zakiah; Dian Widya Putri; Nila Nurlimah; Dadan Mulyana; Nurhastuti Nurhastuti (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Korean waves have penetrated Indonesian youth and become popular among them. Various studies show that Korean culture is an object of imitation for Indonesian teenagers. Imitation starts from the presentation of culture, then the process of internalizing culture in adolescents and finally teenagers makes Korean culture a part of them. Korean culture for Indonesian teenagers is structured. Korean teenage artists have drilled faces to become agents of the spread of Korean culture. The method used in the literature study is the results of research by several universities in Indonesia, with the theory of cultural dynamics which says that culture always changes. Cultural change through the process of diffusion, acculturation and assimilation. The results showed the spread of mass media, especially Korean online media that has an agenda to campaign Korean culture. While the cultural material of Korea that diffused is drama, music, fashion, food, and language. The target audienss for all those materials are teenagers and adult except for music, which is more desirable by the early teenagers. The positive impact on viewers is learning to save, to do business, to gain experience and to make new friends. The negative impacts are wasteful, fan war, pornography and porno action, and loves Korean culture than its own culture.